Change of eruptive style during Pliocene deglaciation: from scoria cones to lava shields in southern extra-Andean Patagonia, Argentina - Gonzalez Guillot, Mauricio Alberto; Ponce, Juan Federico (Bulletin of Volcanology)
Slab window basalt cycles in extra-Andean Patagonia formed in a main-plateau and a post-plateau stage, during glacial and interglacial events. Here, we provide field, geochemical and geochronological data of Pliocene basalts and volcanoes from the north of Viedma lake (49° 20′–49° 30′ S). These basalts share the alkaline composition and enrichment in incompatible elements of post-plateau lavas, in agreement with their radiometric ages. While most post-plateau basalts were erupted through scoria cones, we found that some effusions to the west built lava shields of scutulum type. Field evidence indicates that shields formed during or soon after deglaciation, whereas scoria cones formed before ice retreat or at interglacial stages. We obtained an Ar/Ar age of 3.59 ± 0.07 Ma for a pre-shield basalt, extruded immediately before or concomitant with till deposition. Lava shield formation occurred soon after this age. The lava shield basalts are enriched in incompatible elements. Their petrogenesis involved low degree (~ 2.5%) partial melting of a garnet lherzolite source at the waning of the post-plateau stage, followed by stagnation and high pressure fractionation. Subsequent low pressure fractionation also occurred during ascent. Pre-shield basalts evolved by slightly greater degree of partial melting (~ 3–3.5%) and lesser fractionation. We propose that during glaciation, glacial loading favoured magma ponding, probably at the base of the crust, and that during/after deglaciation lithospheric relaxation facilitated tapping of stored, more evolved magmas. Stagnation favoured outgassing, so that low ascent and eruption rates of outgassed magma triggered a change to an effusive style. Fil: Gonzalez Guillot, Mauricio Alberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Universidad Nacional de Tierra del Fuego, Antártida e Islas del Atlántico Sur. Instituto de Ciencias Polares, Ambientales y Recursos Naturales; Argentina Fil: Ponce, Juan ...